Tespa1 Deficiency Dampens Thymus-Dependent B-Cell Activation and Attenuates Collagen-Induced Arthritis in Mice - Yao, Yunliang; Huang, Wei; Li, Xiaoyu; Li, Xiawei; Qian, Jin; Han, Hui; Sun, Hui; An, Xiangli; Lu, Linrong; Zhao, Hongxing (Frontiers in Immunology, 2018)
Thymocyte-expressed, positive selection-associated 1 (Tespa1) plays an important role in both T cell receptor (TCR)-driven thymocyte development and in the FcεRI-mediated activation of mast cells. Herein, we show that lack of Tespa1 does not impair B cell development but dampens the in vitro activation and proliferation of B cells induced by T cell-dependent (TD) antigens, significantly reduces serum antibody concentrations in vivo and impairs germinal center formation in both aged and TD antigen-immunized mice. We also provide evidence that dysregulated signaling in Tespa1-deficient B cells may be linked to CD40-induced TRAF6 degradation, and subsequent effects on 1-phosphatidylinositol-4,5-bisphosphate phosphodiesterase gamma-2 (PLCγ2) phosphorylation, MAPK activation, and calcium inﬂux. Furthermore, we demonstrate that Tespa1 plays a critical role in pathogenic B cells, since Tespa1-deficient chimeric mice showed a lower incidence and clinical disease severity of collagen-induced arthritis. Overall, our study demonstrates that Tespa1 is essential for T cell-dependent B cell responses, and suggests an important role for Tespa1 during the development of autoimmune arthritis.